2014
DOI: 10.1007/s10916-014-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient RFID Authentication Protocol to Enhance Patient Medication Safety Using Elliptic Curve Cryptography

Abstract: Medication errors are very dangerous even fatal since it could cause serious even fatal harm to patients. In order to reduce medication errors, automated patient medication systems using the Radio Frequency Identification (RFID) technology have been used in many hospitals. The data transmitted in those medication systems is very important and sensitive. In the past decade, many security protocols have been proposed to ensure its secure transition attracted wide attention. Due to providing mutual authentication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 18 publications
0
56
0
1
Order By: Relevance
“…Personal Digital Assistant (31) 1 (5) ADM** Dura A tecnologia de Radio Frequency Identification (RFID) permite a captura automática de dados para identificação de objetos providos de dispositivos eletrônicos, hardwares (etiquetas eletrônicas, tags ou transponders) que emitem sinais de radio frequência para leitores que captam estas informações (15)(16)(17)(18)(19) . O Bar-Code-Assisted Medication Administration (BCMA) (23)(24)(25) e Personal Digital Assistant (PDA) (31) são sistemas de leitura de código de barras projetado para evitar erros de medicação na administração, podendo ser registrado pelo Electronic Medication Administration Record (eMAR) (26)(27) .…”
Section: (5) Prescrição Duraunclassified
“…Personal Digital Assistant (31) 1 (5) ADM** Dura A tecnologia de Radio Frequency Identification (RFID) permite a captura automática de dados para identificação de objetos providos de dispositivos eletrônicos, hardwares (etiquetas eletrônicas, tags ou transponders) que emitem sinais de radio frequência para leitores que captam estas informações (15)(16)(17)(18)(19) . O Bar-Code-Assisted Medication Administration (BCMA) (23)(24)(25) e Personal Digital Assistant (PDA) (31) são sistemas de leitura de código de barras projetado para evitar erros de medicação na administração, podendo ser registrado pelo Electronic Medication Administration Record (eMAR) (26)(27) .…”
Section: (5) Prescrição Duraunclassified
“…First, for the improved RFID authentication protocol, the main design constraints are directly related to the challenging limitations of the RFID technology in terms of computation time, communication, power consumption, and storage memory. It can be observed that the improved protocol could overcome security weaknesses noted in previous protocols and is more secure (or with equivalent security performance) than the most recent related protocols . The improved protocol uses only a one‐way hash function to ensure the security and privacy of the exchanged information between the different components of the RFID system.…”
Section: Performance Analysis and Comparisonmentioning
confidence: 99%
“…Further [38] proposed an ECC-based RFID authentication scheme using ECC and a one-way hash function.But, unfortunately, Chou's scheme also faced various failures. In [39] it is pointed out that Chou' scheme suffers from the key compromise problem. Moreover, M.Farash [40] have shown that Chou's scheme was vulnerableto the impersonation attack and proposed an improved scheme to overcome those attacks.…”
Section: Security Requirements For Rfid Communication Includesmentioning
confidence: 99%